Jahresbericht des Vereins Kunsthalle Bern 1989 / 90. - Hahnloser, Bernhard; Kunsthalle Bern (Bern : Kunsthalle Bern, 1990)
Bustamante, Jean-Marc ; Dumas, Marlene ; Vercruysse, Jan ; Pistoletto, Michelangelo ; Schütte, Thomas ; etc.
Duits
boek